Quantitative pharmacology of denosumab in patients with bone metastases from solid tumors. (March 2015) - Ruixo, Juan Jose Perez; Doshi, Sameer; Sohn, Winnie; Chow, Andrew; Korth‐Bradley, Joan; Mager, Donald; Meibohm, Bernd; Zhou, Hong Hui
Abstract Denosumab (XGEVA®) is a recombinant, fully human IgG2 monoclonal antibody directed against the receptor activator of nuclear factor kappa‐B ligand (RANKL) that prevents differentiation of osteoclast precursors into mature osteoclasts and acceleration of bone resorption, resulting in the inhibition of osteoclast activation. Denosumab is indicated for the prevention of skeletal‐related events (SREs) in adult patients with bone metastases from solid tumors at the dose of 120 mg administered subcutaneously (SC) every 4 weeks. This review is focused on describing its target‐mediated disposition and direct inhibitory effect on bone resorption, as well as the modeling and simulation techniques used to integrate the PKPD information collected during clinical development of denosumab. In addition, this review further discusses the clinical relevance of patient covariate effects on denosumab systemic exposure, target engagement and downstream pharmacodynamics biomarkers, and the rationale for dosing regimen selection for Phase 3 studies. Phase 3 clinical studies demonstrated that denosumab was superior to zoledronic acid in inhibiting bone resorption and, consequently, delaying the time to first SRE by a median of 8.2 months in patients with bone metastases from solid tumors. Thus, denosumab may be considered a better alternative treatment than zoledronic acid for the prevention of SRE in patients with bone metastases from solid tumors.